Development and Optimization of a Multiplex Real-Time RT-PCR to Detect SARS-CoV-2 in Human Samples - Camilo Castellar-Mendoza; María-Angélica Calderón-Peláez; Jaime E. Castellanos; Myriam L. Velandia-Romero; Carolina Coronel-Ruiz; Sigrid Camacho-Ortega; Lilia J. Bernal-Cepeda; Lady López-Ibarra; Jhann A. Arturo; Félix G. Delgado; Hernando Gutierrez-Barbosa; Sonia Bohorquez-Avila; et al. (International Journal of Microbiology)
PCR and its variants (RT-PCR and qRT-PCR) are valuable and innovative molecular techniques for studying nucleic acids. qPCR has proven to be highly sensitive, efficient, and reproducible, generating reliable results that are easy to analyze. During the COVID-19 pandemic, qPCR became the gold standard technique for detecting the SARS-CoV-2 virus that allowed to confirm the infection event, and those asymptomatic ones, and thus save millions of lives. In-house multiplex qPCR tests were developed worldwide to detect different viral targets and ensure results, follow the infections, and favor the containment of a pandemic. Here, we present the detailed fundamentals of the qPCR technique based on fluorogenic probes and processes to develop and optimize a successful multiplex RT-qPCR test for detecting SARS-CoV-2 that could be used to diagnose COVID-19 accurately.